Layanan Bank Syariah Berbasis Multikultural - Ami'in, Siti Nur; Janah, Tutik Nurul (JIOSE: Journal of Indonesian Sharia Economics, 2023)
This study aims to reveal how multicultural-based services exist in PT. BPRS Artha Mas Abadi, and aims to prove that Islamic bank services are for all people and are universal. This study uses descriptive-qualitative, and data obtained from direct interviews with one of the executive officers at PT BPR Syariah Artha Mas Abadi and other sources which are collected and analyzed descriptively. This study shows that PT BPR Syariah Artha Mas Abadi's customers come from diverse communities. Evidence that Islamic bank services at PT BPR Syariah Artha Mas Abadi are multicultural-based services that do not discriminate between religion, ethnicity and culture as well as the professional background of its customers is that it has 52 non-Muslim savings customers and 10,918 Muslims with a customer background who come from various tribes and cultures as well as diverse customer professions. As for financing services, PT BPRS Artha Mas Abadi has 18 non-Muslim customers and 1,362 Muslim customers. This study suggests the need for a more massive role of the government and sharia banking practitioners to increase literacy and education to all people, both Muslim and non-Muslim, about sharia bank services.